Triage in Disaster Management - Ozkan, Seda; Ikizceli, Ibrahim (Cerrahpaşa Medical Journal, 2023)
According to the World Health Organization, a disaster is an ecological phenomenon that is large and sudden enough to require foreign aid. Disaster disrupts health services in the affected community or region. The use of “disaster triage” in disaster response is considered the cornerstone in the management of mass injuries. Disaster triage systems allow rapid identification of critical injury without detailed investigation in a complex mass accident environment. In routine triage, patients with life-threatening and multiple system injuries are treated primarily. In disaster triage, if the number of injured is higher than the available medical resources, the patients who have a better chance of survival and require less time, material, and personnel in their intervention are given priority. In this way, secondary disasters are prevented in hospitals; morbidity, complications, and late deaths are reduced; survival is increased with appropriate treatment; and resources are used appropriately. Disaster triage is divided into 2 as triage applied in the field and in the hospital. Disaster triage applied in the field has 3 stages. In the first stage, casualties are quickly divided into triage categories according to their urgency. In the second stage of triage in the field, the injured are re-evaluated in the field, and treatment and referral priorities are determined. In the third stage of triage in the field, communication-based triage is applied. In this article, it is aimed to explain disaster triage, which should be applied both in the field and in the hospital environment, and the most commonly used triage systems. Cite this article as: Ozkan S, Ikizceli I. Triage in disaster management. Cerrahpaşa Med J 2023;47(S1):9-16